Era New Normal; Analysis Of Factors That Influence Community Drinking Coffee In Coffee In Surabaya City - Asmirin Noor; Tri Cicik Wijayanti; Moh. Dwi Kharis Rifai; Sofyan Lazuardi (Cita Konsultindo Research Center, 2022)
AbstractThis research is entitled Analysis of Factors Influencing People To Drink Coffee at Coffee Shops in Surabaya City. The research population is a coffee shop in Surabaya by taking a sample of 26 respondents. The research uses a quantitative research approach with factor analysis. The experimental factors are Product, Price, Place, Promotion, and Service Quality, consisting of 21 variables. In stage 1 analysis, only 20 variables can be used to perform factor analysis. The analysis results prove that five formed factors can influence purchasing decisions, and only two factors have a dominant influence on these purchasing decisions, namely factor 1 and factor 4. 1 and 4. In factor 1, there are variables of public relations and direct selling (Promotion) and variables of ease of place access, comfort, and spacious parking (Place), as well as in factor 2; there are variables of product taste (Product) and suitability price with benefits and price competitiveness (Price). Variables in factor 2 and factor 3 have a small correlation value so that it does not significantly affect purchasing decisions. Meanwhile, factor 5 has a negative correlation value, which means that the more the variable can be paid off and reliability will decrease the decision to buy a drink at a coffee shop in Surabaya